Backfire - Coulter, Catherine (Coulter, Catherine. FBI thrillers, 2012)
When a San Francisco judge is shot at the same time a once-relentless federal prosecutor turns cautious, FBI agents Lacey Sherlock and Dillon Savich receive an ominous note from the culprit that blames them for the incident.